Friction velocity dependence, cohesion, and XRD data of marine sediments from IODP Site U1301, Juan de Fuca plate - Stanislowski, Katja; Roesner, Alexander; Ikari, Matt J (PANGAEA, 2022)
To investigate the lithostratigraphic position and frictional behavior of the shallow plate boundary fault at the northern Cascadia subduction zone, we conducted laboratory friction experiments on sediments recovered at IODP Site U1301. We used a single-direct shear device under room temperature conditions with 3.5% simulated seawater to perform cohesion tests, plate rate tests and velocity step tests (VST). Friction data from VSTs were inversly modelled to obtain rate- and state friction (RSF) parameters.
Keywords: Cascadia Basin; earthquake; fault; Juan de Fuca plate; laboratory friction experiments; subduction zone input